Adaptations to the welsh national exercise referral scheme during the COVID-19 pandemic: a qualitative study exploring the experiences of service users and providers and supplementary out-of-pocket cost analysis - Newby, Katie; Howlett, Neil; Wagner, Adam P.; Lloyd, Nigel; Freethy, Imogen; Bontoft, Charis; Fakoya, Olujoke; Jackson, Shelley; Jackson, Carla; Wills, Wendy; McKibben, Mary-Ann; Petherick, Annie; et al. (BMC public health, 2025)
Background Despite the proliferation of exercise referral schemes in the UK, evidence on their efficacy is equivocal. The Welsh National Exercise Referral Scheme (NERS) is heavily used but inequalities in uptake have been reported. As a result of the COVID-19 pandemic, NERS was initially suspended and then transitioned from standard face-to-face delivery to alternative remote methods, including virtual delivery. The aim of this study was to explore the barriers and facilitators to uptake and engagement of NERS when delivered in face-to-face and virtual formats, and to examine the cost to service users of engaging with the scheme in these different ways. Methods This was a qualitative study with supplementary cost analysis. Maximum variation sampling was used to recruit participants. Interviews with service users ( n = 21) and one person who declined the service, and three focus groups with service providers ( n = 19), were conducted. Framework analysis was used to analyse the qualitative data. Quantitative data obtained through the interviews on service users’ out-of-pocket costs of attending face-to-face or virtual classes were summarised using descriptive statistics. Results Five themes were identified from the qualitative analysis which summarised barriers and facilitators to uptake and engagement as perceived and experienced by the different stakeholders. Themes included: opaqueness and uncertainty around referral; Exercise Referral Professionals allaying concerns and providing reassurance at scheme entry; the mixed appeal and accessibility of virtual delivery; factors that support ongoing engagement; and personal and financial circumstances restricting uptake and engagement. Conclusions This study indicates that offering a virtual version of NERS could make the scheme more accessible to those who are typically underserved, provided strategies to address digital inclusion are addressed. Findings provide wider evidence to inform adaptations that could be made to ensure that other exercise referral schemes can optimise virtual delivery.